Minimization of eddy-current loss in a permanent-magnet tubular linear motor - Abdalla, I.I. (Insight Society, 2017)
This paper presents a minimization of eddy-current loss (ECL) in permanent-magnet (PM) of three tubular linear PM motors (TLPMMs). Three-dimensional Finite-Element Analysis has been used for the simulations. The ECL component is usually not taken into consideration in conventional PM motors. In present technologies, ECL is generated inside magnets of PM motors, due to both the high conductivity of the rare-earth magnets and the harmonics of the slot. This loss can increase the temperature inside the magnets, and that may deteriorate their magnetic properties and potential risk of thermal demagnetization. Therefore, in the translator, segmented magnets has been used, because the cancellation of the ECL with this technique is possible as illustrated by the FEA results. Meanwhile, for the stator core of the three proposed motors, soft magnetic composite (SMC) material, Somaloy 700 has been used for its low cost and approximately zero ECL.